METHODOLOGICAL PROBLEMS OF ASSESSING THE EFFECTIVENESS OF PUBLIC ADMINISTRATION OF SOCIO-ECONOMIC DEVELOPMENT - Bukhovets, Tatyana (Economy and Sociology, 2024)
The need for theoretical, methodological and scientific substantiation of new ways to improve the effectiveness of public administration as well as for the development of a single comprehensive methodological approach to its assessment increases every year in the context of increasing demands of society to the quantity and quality of services provided by the state and the effectiveness of decisions taken by state bodies at the national and local levels. The purpose of the study is to identify the main problems and justify the methodological provisions for assessing the effectiveness of public administration. The study is based on the application of general scientific and special methods, as well as interdisciplinary approach, taking into account the provisions of the history and theory of public administration, economic science, political science, sociology, statistical theory, theory of regional studies, etc. The author develops the comprehensive methodological approach to assess the effectiveness of public administration, taking into account its multifaceted nature and complexity. The approach presents a toolkit and a step-by-step algorithm for assessing the effectiveness of public administration. It formulates the fundamental principles of assessment, substantiates the need to determine the object of assessment and type of effectiveness, which determine the specific purpose and objectives of assessment, as well as the relevant criteria, indicators and methods. At the last stages of the assessment, emphasis is placed on the importance of correct and accurate interpretation of the results obtained and the development of recommendations to eliminate identified bottlenecks and improve the effectiveness of public administration.